Formation of a ternary complex for selenocysteine biosynthesis in bacteria - Silva, Ivan Rosa; Serrao, Vitor Hugo Balasco; Manzine, Livia Regina; Faim, Livia Maria; Silva, Marco Tulio Alves da; Makki, Raphaela; Saidemberg, Daniel Menezes [UNESP]; Cornelio, Marinonio Lopes [UNESP]; Palma, Mario Sergio [UNESP]; Thiemann, Otavio Henrique (The American Society for Biochemistry and Molecular Biology, 2015)
The synthesis of selenocysteine-containing proteins (selenoproteins) involves the interaction of Selenocysteine Synthase (SelA), tRNA (tRNASec), Selenophosphate Synthetase (SelD, SPS), a specific elongation factor (SelB) and a specific mRNA sequence known as SElenocysteine Insertion Sequence (SECIS). Because selenium compounds are highly toxic in the cellular environment, the association of selenium with proteins throughout its metabolism is essential for cell survival. In this study, we demonstrate the interaction of SPS with the SelA-tRNASec complex, resulting in a 1.3 MDa ternary complex of 27.0 ± 0.5 nm in diameter and 4.02 ± 0.05 nm in height. To assemble the ternary complex, SPS undergoes a conformational change. We demonstrated that the glycine-rich N-terminal region of SPS is crucial for the SelA-tRNASec-SPS interaction and selenoprotein biosynthesis, as revealed by functional complementation experiments. Taken together, our results provide new insights into selenoprotein biosynthesis, demonstrating for the first time the formation of the functional ternary SelA-tRNASec-SPS complex. We propose that this complex is necessary for proper selenocysteine synthesis and may be involved in avoiding the cellular toxicity of selenium compounds.
Keywords: Rna-protein interaction; Bacteria; Protein complex; Selenocysteine; Transfer RNA (tRNA)